Prognostic Factors for Postsurgical Recovery of Deltoid Palsy due to Cervical Disc Herniations - Chung, Jae-Yoon; Park, Jong-Beom; Chang, Han; Song, Kyung-Jin; Kim, Jin-Hyok; Hong, Chang-Hwa; Lee, Jung Sub; Lee, Sang-Hun; Song, Kwang-Sup; Yang, Jae Jun; Uh, Jae-Hyung; Kim, Young-Tae; et al. (Asian spine journal, 2015)
Retrospective multicenter study. We aimed to investigate prognostic factors affecting postsurgical recovery of deltoid palsy due to cervical disc herniation (CDH). Little information is available about prognostic factors affecting postsurgical recovery of deltoid palsy due to CDH. Sixty-one patients with CDH causing deltoid palsy (less than grade 3) were included in this study: 35 soft discs and 26 hard discs. Average duration of preoperative deltoid palsy was 11.9 weeks. Thirty-two patients underwent single-level surgery, 22 two-level, four three-level, and three four-level. Patients with accompanying myelopathy, shoulder diseases, or peripheral neuropathy were excluded from the study. Deltoid palsy (2.4 grades vs. 4.5 grades, p<0.001) and radiculopathy (6.4 points vs. 2.1 points, p<0.001) significantly improved after surgery. Thirty-six of 61 patients (59%) achieved full recovery (grade 5) of deltoid palsy, with an average time of 8.4 weeks. Longer duration of preoperative deltoid palsy and more severe radiculopathy negatively affected the degree of improvement in deltoid palsy. Age, gender, number of surgery level, and disc type did not affect the degree of improvement of deltoid palsy. Contrary to our expectations, severity of preoperative deltoid palsy did not affect the degree of improvement. Due to the shorter duration of preoperative deltoid palsy, in the context of rapid referral, early surgical decompression resulted in significant recovery of more severe grades (grade 0 or 1) of deltoid palsy compared to grade 2 or 3 deltoid palsy. Early surgical decompression significantly improved deltoid palsy caused by CDH, irrespective of age, gender, number of surgery level, and disc type. However, longer duration of deltoid palsy and more severe intensity of preoperative radiating pain were associated with less improvement of deltoid palsy postoperatively.